An affordable platform for automated synthesis and electrochemical characterization - Pablo-García, Sergio; García, Ángel; Akkoç, Gün Deniz; Sim, Malcolm; Cao, Yang; Somers, Maxine; Hattrick, Chance; Yoshikawa, Naruki; Dworschak, Dominik; Hao, Han; Aspuru-Guzik, Alán (Device, 2024)
Electrochemical techniques are pivotal for materials discovery and renewable energy; however, often the extensive chemical spaces to be explored require high-throughput experimentation to ensure timely results, which are costly for both instruments and materials/consumables. While self-driving laboratories (SDLs) promise efficient chemical exploration, most contemporary implementations demand significant time, economic investment, and expertise. This study introduces an open and cost-effective autonomous electrochemical setup comprising a synthesis platform and a custom-designed potentiostat device. We present an automated electrochemical module for SDLs that offers rapid deployment and extensive control over electrochemical experiments compared to commercial alternatives. Using ChemOS 2.0 for orchestration, we showcase our setup's capabilities through a campaign reacting different metal ions with ligands to form coordination compounds, yielding a database of 400 electrochemical measurements. Committed to open science, we provide the potentiostat design, campaign software, and raw data, aiming to democratize customized components in SDLs and ensure transparent data sharing and reproducibility.
CRIS-Team Scopus Importer:2024-11-08
Keywords: DTI-3: Develop